2021
DOI: 10.3389/fgene.2021.666136
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Biallelic TLE6 Variants in Female Infertility With Preimplantation Embryonic Lethality

Abstract: Preimplantation embryonic lethality is a rare cause of primary female infertility. It has been reported that variants in the transducin-like enhancer of split 6 (TLE6) gene can lead to preimplantation embryonic lethality. However, the incidence of TLE6 variants in patients with preimplantation embryonic lethality is not fully understood. In this study, we identified four patients carrying novel biallelic TLE6 variants in a cohort of 28 patients with preimplantation embryonic lethality by whole-exome sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In mouse models, the knockout of the Tle6 gene has no effect on oogenesis but results in embryonic developmental arrest at the 2-cell stage, leading to female mouse infertility [ 48 , 67 ]. Homozygous and compound-heterozygous variants in the TLE6 gene are associated with various phenotypes, including fertilization failure, early cleavage failure, embryonic developmental arrest on day 3, and a high rate of embryo fragmentation due to the disruption of F-actin and spindle assembly [ 14 , 66 , 68 , 69 ]. A woman with a heterozygous variant in TLE6 had normal fertility and two healthy children [ 69 ].…”
Section: Genes Of Scmc Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mouse models, the knockout of the Tle6 gene has no effect on oogenesis but results in embryonic developmental arrest at the 2-cell stage, leading to female mouse infertility [ 48 , 67 ]. Homozygous and compound-heterozygous variants in the TLE6 gene are associated with various phenotypes, including fertilization failure, early cleavage failure, embryonic developmental arrest on day 3, and a high rate of embryo fragmentation due to the disruption of F-actin and spindle assembly [ 14 , 66 , 68 , 69 ]. A woman with a heterozygous variant in TLE6 had normal fertility and two healthy children [ 69 ].…”
Section: Genes Of Scmc Componentsmentioning
confidence: 99%
“…Homozygous and compound-heterozygous variants in the TLE6 gene are associated with various phenotypes, including fertilization failure, early cleavage failure, embryonic developmental arrest on day 3, and a high rate of embryo fragmentation due to the disruption of F-actin and spindle assembly [ 14 , 66 , 68 , 69 ]. A woman with a heterozygous variant in TLE6 had normal fertility and two healthy children [ 69 ]. In men with homozygous variants in TLE6 fertility is preserved [ 14 ].…”
Section: Genes Of Scmc Componentsmentioning
confidence: 99%
“…Increasing evidence indicates additional functions of SCMCs, including mitochondrial distribution and translational regulation (Bebbere et al., 2016; Lu et al., 2017). Recently, several MEGs were identified in human by whole‐exome sequencing (Alazami et al., 2015; M. Zhang et al., 2021). For domestic animals, Bebbere et al first reported expression of SCMC genes in ovine oocytes and pre‐implantation embryos, representing the first expression profiles for a large mammalian species (Bebbere et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…SCMCs, which appear to be functionally conserved across many mammalian species, include eight proteins: oocyte‐expressed protein, zinc finger BED domain‐containing protein 3, KH domain‐containing protein 3, protein‐arginine deiminase type 6 (PADI6), transducin‐like enhancer protein 6 (TLE6), NOD‐like receptor family pyrin domain‐containing 2 (NLRP2), NLRP5 and NLRP7 (Mahadevan et al., 2017; Monk et al., 2017; Xu et al., 2016; M. Zhang et al., 2021; Zhu et al., 2015). The study of MEGs has mainly focused on humans and mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation